Vitamin A deficiency attenuates cardiac rupture in Stra6-deficient hearts following ischemic injury - Smolenski, Yannick; Froese, Natali; Galuppo, Paolo; Werlein, Christopher; Gigina, Anna; Talbot, Steven R.; Erschow, Sergej; Wedekind, Dirk; Geffers, Robert; Ghyselinck, Norbert B.; Bähre, Heike; Kamp, Jan C.; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundStimulated by retinoic acid gene 6 (STRA6) is a cell surface receptor that regulates cellular uptake of vitamin A metabolites and cardiac development. We hypothesized that Stra6 expression attenuates ischemic injury-induced heart failure following myocardial infarction (MI) by vitamin A-dependent mechanisms.MethodsMI was induced in mice with Stra6 germline deletion, vitamin A deficiency (VitAD) by combined lecithin-retinol acyltransferase (Lrat) germline deletion and feeding with a vitamin A-deficient diet. Contractile function was determined by transthoracic echocardiography, cardiac structure was assessed by histological analysis, and gene profiling was performed by RNA sequencing.ResultsStra6 deletion and VitAD did not impact contractile function and cardiac structure under basal conditions. Stra6 deficiency resulted in myocardial rupture, with the majority of mice dying by 4 days post-MI, which additional VitAD attenuated. Interestingly, contractile function, mRNA expression of heart failure markers, and cardiac structure were not different between groups 3 days post-MI. Gene profiling 3 days post-MI revealed decreased Wnt signaling in Stra6-deficient relative to wildtype hearts, which was reversed by VitAD.ConclusionThe present study identifies an unexpected role for VitAD, which preserves Wnt signaling and attenuates cardiac rupture in Stra6-deficient hearts following ischemic injury.